Contemporary Artistic Domain among Digital Environment in the Canadian Arctic - Aurélie Maire (Anthropologie et Sociétés, 2011)
The access of digital technologies in the Canadian Arctic represents a main asset, on a sociocultural level as well as on a political and economical level, even more important that this step matches with two strong values among Inuit societies : opening to the world and demand of visibility. Internet gives people the opportunity to share their individual and collective experiences giving priority to the word, in Nunavut as elsewhere. When the digital duplication of artworks and knowledge is easily accessible, the management of copyright systems established in the 1950’s are reappraised nowadays, as new concerns about ethics and moral rights occur. Following a theoretical and methodological approach derived from anthropology, ethnolinguistics and history of art, this research note engages a reflection on sociocultural issues that are inherent to the use of Internet within the contemporary artistic domain in the Canadian Arctic. Focusing on the double question of copyright and intellectual property, the discussion aims to understand the system of Inuit values that revolved around it, in connexion with the notion of property of ideas. Dans l’Arctique canadien, l’accès aux technologies numériques représente un atout majeur, tant au niveau socioculturel que politique et économique, du fait que sa démarche s’inscrit dans deux valeurs hautement prisées dans les sociétés inuit : l’ouverture sur le monde et l’exigence de visibilité. Au Nunavut comme ailleurs, Internet permet de partager les expériences individuelles et collectives, en privilégiant la prise de parole. Dans un contexte où la reproductibilité numérique des oeuvres d’art et des savoirs devient aisément accessible, les modes de gestion des droits d’auteur établis dès les années 1950 sont aujourd’hui remis en question alors que de nouvelles préoccupations d’ordre éthique et moral interviennent. Selon une approche théorique et méthodologique empruntée à l’anthropologie, l’ethnolinguistique et l’histoire de l’art, cette note de recherche propose une réflexion ...